Empowerment of Groups of Society Through Creative Economy Production Convection and Sablon in SMPS PTPN 4 Dolok Ilir Simalungun - Tulus; Marpaung, T.J.; Suriati; Marpaung, J.L.; Marpaung, Rony; Sutanto, Freddy (Talenta Publisher, 2023)
Shirt sablon activities are the most exciting activity for the moment, given that the shirt will always be sought and bought by the community. Shirt templates are techniques of printing pictures, photos, cartoons, typography and various other design results to the shirt surface. Which means the core of the next shirt making besides thinking about the material is the design that will be sued. This activity aims to improve skills and capabilities in terms of increasing the economic value of a pure shirt into a shirt that has a sale value, economically of course this skill can be a sufficient supply to plunge into an industry if later Master and Students of SMPS PTPN 4 Dolok Ilir want to plung into the world of creative industry confectionery and templates. The result achieved is the independence of SMPS PTPN 4 Dolok Ilir in the enterprise world both at school and in the community.